An Amphiphobic Hydraulic Triboelectric Nanogenerator for a Self‐Cleaning and Self‐Charging Power System. (11th July 2018) - Zhang, Qian; Liang, Qijie; Liao, Qingliang; Ma, Mingyuan; Gao, Fangfang; Zhao, Xuan; Song, Yiding; Song, Lijuan; Xun, Xiaochen; Zhang, Yue
Abstract: Raindrop falling, which is one kind of water motions, contains large amount of mechanical energy. However, harvesting energy from the falling raindrop to drive electronics continuously is not commonly investigated. Therefore, a self‐cleaning/charging power system (SPS) is reported, which can be exploited to convert and store energy from falling raindrop directly for providing a stable and durable output. The SPS consists of a hydraulic triboelectric nanogenerator (H‐TENG) and several embedded fiber supercapacitors. The surface of H‐TENG is amphiphobic, enabling the SPS self‐cleaning. The fiber supercapacitor which uses α‐Fe2 O3 /reduced graphene oxide composite possesses remarkable specific capacitance, excellent electrical stability, and high flexibility. These properties of the fiber supercapacitor make it suitable for a wearable power system. A power raincoat based on the SPS is demonstrated as application. After showering by water flow, which simulates falling raindrops, for 100 s, the power raincoat achieves an open‐circuit voltage of 4 V and lights a light‐emitting diode for more than 300 s. With features of low cost, easy installation, and good flexibility, the SPS harvesting energy from the falling raindrop renders as a promising sustainable power source for wearable and portable electronics. Abstract : A self‐cleaning and self‐charging power system (SPS) is developed. The SPS transforms the kinetic energy of water energy into electric energy and stables charge‐discharge of the transformed energy all in one. After showering the SPS with water, electric energy can be provided to power a light emitting diode sustainably.